Thermal (geothermal) hot springs list for the United States - National Geophysical Data Center / World Data Service (NGDC/WDS); George Berry; Paul J Grim; Joy A Ikelman (PANGAEA, 2025)
The Thermal Springs List for the United States contains data from 1661 hot springs in the continental U.S., Hawaii, and Alaska. The content has not been updated since its initial publication in 1980. Geothermics is the study of heat generated in Earth extquotesingles interior and its manifestation at the surface. The NOAA National Centers for Environmental Information has a variety of publications and data sets which provide information on the location, magnitude, and potential uses of geothermal resources. The publication, "Thermal Springs List for the United States" (1981) is a compilation of 1,700 thermal springs locations in 23 states. The list gives the geographic locations of thermal springs by state, and is sorted by degrees of latitude and longitude within the state. It contains the name of each spring (where available), maximum surface temperature (in both degrees Fahrenheit and degrees Celsius), name of corresponding USGS 1:2,500,000-scale (AMS) map, largest scale USGS topographic map coverage available (either 7.5 or 15-min. quadrangle), and cross-references. Thermal springs listed include natural surface hydrothermal features (springs, pools, mud pots, mud volcanoes, geysers, fumaroles, and steam vents) at temperatures of 20 degrees Celsius (68 degrees Fahrenheit) or higher. They do not include wells or mines, except at sites where they supplement or replace natural vents that have been active recently or at sites where orifices are indistinguishable as natural or artificial. The thermal springs data from this publication are also available on-line. This dataset has been archived in the framework of the PANGAEA US data rescue initiative 2025.